Passage of molecules through the wall of the gastrointestinal tract. II. Application of low-molecular weight polyethyleneglycol and a deterministic mathematical model for determining intestinal permeability in man. Issue 3 (March 1980) - Sundqvist, T; Magnusson, K E; Sjödahl, R; Stjernström, I; Tagesson, C
Abstract : The intestinal permeability to low molecular weight polyethyleneglycol (PEG) has been evaluated by means of a simple mathematical model and computer-aided curve-fitting procedures. Macrogolum 400, a mixture of 11 PEGs with molecular weights ranging from 194 to 634 daltons, was taken together with a liquid meal and a six-hour portion of urine collected. The different PEGs were then extracted from the urine, separated from each other by gas-liquid chromatography, and the relative peak area of each individual PEG determined. The distribution of different PEGs in the urine was then compared with the original PEG-distribution in three different ways: (1) by comparing the median values of the molecular weights, (2) by comparing the mean and standard deviation after curve fitting to the normal distribution, and (3) by curve fitting to mathematical filter functions demonstrating molecular exclusion due to size. It thus appeared that molecules were excluded both in the high and in the low molecular weight range, possibly by a combined effect of the intestinal permeability barrier and an escape to other compartments than the urine. However, relatively more of the larger PEGs passed from the intestine to the urine in a patient with Crohn's disease than in an apparently healthy individual.